A Systematic Survey of Moon-forming Giant Impacts. I. Nonrotating Bodies - Miles Timpe; Christian Reinhardt; Thomas Meier; Joachim Stadel; Ben Moore (The Astrophysical Journal, 2023)
In the leading theory of lunar formation, known as the giant impact hypothesis, a collision between two planet-size objects resulted in a young Earth surrounded by a circumplanetary debris disk from which the Moon later accreted. The range of giant impacts that could conceivably explain the Earth–Moon system is limited by the set of known physical and geochemical constraints. However, while several distinct Moon-forming impact scenarios have been proposed—from small, high-velocity impactors to low-velocity mergers between equal-mass objects—none of these scenarios have been successful at explaining the full set of known constraints, especially without invoking controversial post-impact processes. In order to bridge the gap between previous studies and provide a consistent survey of the Moon-forming impact parameter space, we present a systematic study of simulations of potential Moon-forming impacts. In the first paper of this series, we focus on pairwise impacts between nonrotating bodies. Notably, we show that such collisions require a minimum initial angular momentum budget of approximately 2 J _EM in order to generate a sufficiently massive protolunar disk. We also show that low-velocity impacts ( v _∞ ≲ 0.5 v _esc ) with high impactor-to-target mass ratios ( γ → 1) are preferred to explain the Earth–Moon isotopic similarities. In a follow-up paper, we consider impacts between rotating bodies at various mutual orientations.